Predisposing factors and management of hemodynamic depression following carotid artery stenting - Pachipala Sudheer; Ayush Agarwal; Venugopalan Y Vishnu; M V Padma Srivastava (Annals of Indian Academy of Neurology, 2021)
Carotid artery stenting (CAS) involves dilatation of carotid bulb which can trigger a series of neuronal responses resulting in hemodynamic depression that might influence the outcome of the procedure. This is a frequent but underdiagnosed complication of CAS. Although it is mild, transient and self-limiting in majority of cases, it can result in significant morbidity and mortality if persistent. Neurologists should be aware of the predisposing factors and management of this common complication. In patients who present with stroke following carotid stenting, neurologists should be aware of hypoperfusion secondary to hemodynamic depression as a cause of stroke apart from the stent thrombosis and occlusion.